Technical Aspects Affecting to Jackfruit (Artocarpus Heterophyllus) Beverage Production - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Jackfruit (Artocarpus heterophyllus) is a tropical climacteric fruit. It is one of the commonly consumed foods in Vietnam. Its fesh in fully ripen stage can be eaten directly as a fruit. Jackfruit contains a wide range of phytonutrients such as carotenoids that can act as antioxidants. The jackfruit fesh is highly perishable and ofen undergoes favour loss, tissue sofening, and cut surface browning. During the jackfruit havesting season, excessive supply of the fruit causes the price of jackfruit decreasing dramatically. This fruit is underutilized in commercial scale processing. Therefore we have our tried to add value to the jackfruit fruit. One method of adding value to fresh jackfruit is processing it into drink. We carried out the investigation of extraction (ratio of water: jackfruit, temperature and time of blanching); juicy mixture; preservation. Our result showed that the jackfruit drink having the best quality when extracting with water: jackfruit pulp ratio (70:30) at 85 oC in 3 minutes. The sample was then cooled to 37°C before the addition of pectinase enzyme at 0.09%. The juice was then incubated in a water bath at 37°C in 30 minutes. After the incubation process, the juice was heated in a water bath at 100°C for 2 minutes to inactivate all enzymes present. The hydrolyzed jackfruit juice will be formulated with sugar 2.5%, citric acid 5%, carrageenan 0.06%. Jackfruit drink shelf-life could be maintained for 12 months.Keywords: Jackfruit, Artocarpus heterophyllus, Beverage, Carrageenan, Pectinase, shelf-life